U.S. Attorneys, political control, and career ambition - Miller, Banks P. (Oxford University Press, 2019)
Introduction -- Three case studies in political control -- Principal agent theory, career prospects, and United States Attorneys -- Describing the data and issue areas -- Political responsiveness and case filings -- Political responsiveness and sentence length -- Political responsiveness and career prospects -- Concluding thoughts and implications